Adolph Lewisohn (English edition) Copper Magnate in the "Gilded Age" - Albrecht, Henning (Mäzene für Wissenschaft, 2019)
"New Yorks most valuable citizen" - this honorary title was given to Adolph Lewisohn. When he was born in Hamburg in 1849 as the son of Orthodox Jews and successful merchants, a career as a merchant was put in his cradle. In search of personal freedom he persuaded his strict father in 1867 to let him go to New York. The fact that Lewisohn, as an industrialist in the USA, will generate millions of euros in only twenty years time would have seemed like a fairy tale to the young migrant. With dedication, foresight and flexibility he builds a copper empire. For four decades he then supports countless charitable projects with millions of euros. The Hamburgische Wissenschaftliche Stiftung (Hamburg Scientific Society) also owes him one of the biggest donations it received when it was founded. This is the first biography of this exceptionally successful businessman, art collector and international philanthropist.